Aggregation of dyes in porous glass - Tyurin, Olexandr V.; Bercov, Yury M.; Zhukov, Sergiy O.; Levitskaya, Tetiana F.; Gevelyuk, Sergiy A.; Doycho, Igor K.; Rysiakiewicz-Pasek, Ewa (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The research examines the interaction of dye molecules with their dimers (H aggregates) and the more complex formations (J aggregates) developing in porous glass. The use of porous glass when dealing with dye aggregation has resulted in obtaining photoluminescence dimers of the J aggregating dye, the formation of which is difficult under normal conditions. In addition, the porous glass matrix contributes to a substantial reduction in the interaction of photoexcited states of both a molecular and an aggregated dye, thus helping maximize the luminescence efficiency of porous glass-distributed dyes.
Optica Applicata, Vol. 40, 2010, nr 2, s. 311-321
Keywords: optyka; dye; porous glass; luminescence; aggregates